Effect of feeds and feeding levels over different time periods on the rate of ammonia excretion in Macrobrachium rosenbergii (de Man) - Panikkar, Preetha; Ayyar, S P; Khatre, Shakuntala (Indian Journal of Fisheries, 2016)
The rate of ammonia excretion in Macrobrachium rosenbergii at 2, 4 and 6 h, when fed three commercial feeds and twocontrol feeds at 1%, 5% and 10% of body weight, were investigated. The rate of ammonia excretion was significantlyinfluenced by the quality of feed offered. A higher rate of ammonia excretion by the prawns fed on control feeds ascompared to the commercial feeds appears to be correlated with the protein content in the feeds offered. The quantity offood consumed had significant influence on the ammonia excretion and it was found to increase with feed levels.